WORLD IN THE MANAGEMENT OF INNOVATIVE ACTIVITIES OF ENTERPRISES IN THE CONTEXT OF THE DIGITAL ECONOMY EXPERIENCE - Samadov Sevinchbek (Modern American Journals, 2025)
This article analyzes the activities of major companies such as Amazon, Tesla, Google, Siemens, and Samsung and examines their strategies for implementing technological innovations, supporting new market trends, fostering an innovative culture, investing in digital technologies, implementing digital platforms, and developing new business models.
Keywords: Digital economy, innovative activity, technological investments, innovative culture, digital transformation- digitalization, digital platforms, new business models, global experience, foreign companies.